Evaluation of Post Laryngectomy Pharyngocutaneous Fistula risk Factors - Nitassi, Sophia (Iran J Otorhinolaryngol, 2016)
INTRODUCTION: Pharyngocutaneous fistula (PCF) is the most common complication after total laryngectomy. Its incidence is extremely variable, with values ranging from 3% and 65%. The management of this problem considerably increases the length and the cost of hospitalization. The aim of this study is to analyze the incidence, predisposing factors, and outcome of PCF in patients undergoing total laryngectomy in a Moroccan teaching hospital in Rabat, Morocco. MATERIALS AND METHODS: This study is a retrospective study including 136 patients who underwent total laryngectomy for squamous cell carcinoma of the larynx in our institution, between January 2006 and December 2013. Socio-demographical, biological, surgical, and outcome data were included. Risk factors were analyzed for association with PCF formation. RESULTS: The overall PCF rate was 27.8%. The mean age was 58 (32-82 years). Univariate analysis showed age (P= 0,028), hemoglobin (P=0,026), and previous tracheotomy (P=0,028) to be associated with the onset of PCF. However, multivariate analysis revealed that previous tracheotomy (P=0,028) and low level of preoperative hemoglobin (P=0,026) were highly associated with the occurrence of PCF. CONCLUSION: This is an original work performed in an African country with a large serie. Our findings suggest that age, previous tracheotomy, and low level of haemoglobin are risk factors for PCF onset after total laryngectomy in T4 squamous cell carcinoma.